Dietary taurine supplementation improves breast meat quality in chronic heat‐stressed broilers via activating the Nrf2 pathway and protecting mitochondria from oxidative attack. (24th September 2018) - Lu, Zhuang; He, Xiaofang; Ma, Bingbing; Zhang, Lin; Li, Jiaolong; Jiang, Yun; Zhou, Guanghong; Gao, Feng
ABSTRACT: Background: Chronic heat stress can induce oxidative impairment and decrease breast meat quality in broilers. Taurine is a β ‐amino acid with antioxidant properties. To investigate the alleviative effects and molecular mechanisms of taurine supplementation on breast meat quality in broilers exposed to chronic heat stress, 144 28‐day‐old chickens (Arbor Acres) were randomly distributed to thermoneutral (TN, 22 °C, basal diet), heat stress (HS, consistent 32 °C, basal diet), or heat stress plus taurine (HS + T, consistent 32 °C, basal diet + 5.00 g kg −1 taurine) groups for a 14‐day trial. Results: Chronic heat stress did not affect the contents of moisture, crude protein and crude fat in breast muscle, but impaired breast meat quality in broilers. Taurine supplementation significantly alleviated the increase in lightness and drip loss and the decrease in pH45 min and shear force of breast meat in chronic heat‐stressed broilers. Compared with the HS group, taurine supplementation significantly decreased the levels of reactive oxygen species and malonaldehyde and increased the messenger RNA expressions of nuclear factor erythroid 2‐related factor 2 (Nrf2), NAD(P)H quinone dehydrogenase 1 and heme oxygenase 1 in the HS + T group. Meanwhile, taurine supplementation effectively alleviated mitochondrial damage caused by chronic heat exposure. Conclusion: Dietary taurine supplementation can effectively improve the quality of breast meat in chronic heat‐stressed broilers via activating the Nrf2 pathway and protecting mitochondria from oxidative attack. © 2018 Society of Chemical Industry